Mini-Grid Design Manual - World Bank (Washington, DC, 2014)
The manual has been prepared to encourage, and support the design of improved village electrification schemes, anticipating its usefulness for rural development agencies, as well as for national, and provincial energy companies, and authorities. Theoretical and field experiences describe power mini-grid - i.e., low voltage network within a village, supplied at a single point by a diesel genset, or micro-hydropower plant. The manual focuses on the design of the system to distribute the power generated to consumers, and, designs covered in this manual range from low-cost designs to serve basic lighting needs, to more conventional designs that may become interconnected to the grid within the near future. Discussions on mini-grids do not involve the use of medium voltage (MV), however, it should be recognized that it may occasionally be necessary to use MV to reduce overall costs. The manual includes several examples of mini-grids, to illustrate the context in which such projects have been implemented, with additional detailed case studies. It also contains qualitative descriptions of the issues to be addressed in planning for mini-grids, and a range of design options for the various components of mini-grids, how these are sized, and incorporated into a mini-grid.